German Direct Investments in the Czech Republic – Employment Effects on German Multinational Enterprises - Johannes Schäffler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Do investments in the Czech Republic lead to employment growth or employment losses in the German firms involved? To address this question, a unique database about German firms with foreign direct investments (FDI) in the Czech Republic and firms without FDI in any country has been established. By developing a new method for linking firm-level data with establishment-level data of the Institute for Employment Research (IAB), this database is linked with the IAB employment data. As the exact date of the investments in the Czech Republic is known, the employment development of firms with Czech affiliates and firms without FDI is compared for the same time periods. The analyses show that these groups actually develop differently. One year after the investment, the German workforce of the multinational enterprises (MNEs) shrinks relative to the employment of the reference group. The negative trend continues for some years. However, not all types of jobs are affected negatively. The negative effects refer to medium and low-skilled workers only, whereby the demand for high-skilled workers even increases after the investment.
Keywords: F15; F23; F66; 330